Migration, Workers, and Fundamental Freedoms Pandemic Vulnerabilities and States of Exception in India - Hans, Asha; Kannabiran, Kalpana; Mohanty, Manoranjan (2021)
The COVID-19 pandemic resulted in a mass exodus of India's migrant workers from the cities back to the villages. This book explores the social conditions and concerns around health, labour, migration, and gender that were thrown up as a result of this forced migration. The book examines the failings of the public health systems and the state response to address the humanitarian crisis which unfolded in the middle of the pandemic. It highlights how the pandemic-lockdown disproportionately affected marginalised social groups - Dalits and the Adivasi communities, women and Muslim workers. The book reflects on the socio-economic vulnerabilities of migrant workers, their rights to dignity, questions around citizenship, and the need for robust systems of democratic and constitutional accountability. The chapters also critically look at the gendered vulnerabilities of women and non-cis persons in both public and private spaces, the exacerbation of social stratification and prejudices, incidents of intimidation by the administration and the police forces, and proposed labour reforms which might create greater insecurities for migrant workers. This important and timely book will be of great interest to researchers and students of sociology, public policy, development studies, gender studies, labour and economics, and law.